Depression, anxiety, and stress among inflammatory bowel disease patients during COVID‐19: A UK cohort study. Issue 1 (5th January 2022) - Luber, Raphael P; Duff, Alexa; Pavlidis, Polychronis; Honap, Sailish; Meade, Susanna; Ray, Shuvra; Anderson, Simon H; Mawdsley, Joel; Samaan, Mark A; Irving, Peter M
Abstract: Background and Aim: Patients with chronic diseases are believed to be at increased risk of mental health conditions during the COVID‐19 pandemic. We aimed to assess the incidence of psychological morbidity in inflammatory bowel disease (IBD) patients during the COVID‐19 pandemic, explore for association with risk of severe COVID‐19 and other factors, and establish patients' interest in psychological support. Methods: A survey including the Patient Health Questionnaire‐9, General Anxiety Disorder‐7, and Perceived Stress Scale tools for depression, anxiety, and stress was administered to IBD patients from a tertiary center in London, United Kingdom, in June 2020. Results: Two hundred seventy‐four patients responded to the survey (57% response rate), with 271 (99%) completing it. Moderate–severe depression was observed in 61 (22.5%), while 49 (18%) had moderate–severe anxiety; 39 (14%) had both diagnoses. Mean (SD) stress score was 16.2 (7.4). There was no association between degree of severe COVID‐19 risk and psychological morbidity. Flare symptoms and fatigue were associated with worse psychological morbidity, while accessibility of information regarding COVID‐19 risk and reducing that risk was protective for depression (odds ratio [OR] 0.56 [0.33–0.94], P = 0.03), anxiety (OR 0.62 [0.4–0.96], P = 0.03), and stress (standardized β‐coefficient −0.15 [−0.28 to −0.03], P = 0.02). Seventy‐nine (30%) respondents were interested in receiving psychological support during the pandemic, while 200 (76%) expressed interest beyond the pandemic. Conclusions: Although depression, anxiety, and stress among IBD patients during the pandemic were common, their frequency was similar to pre‐pandemic rates and recent general population levels. Ensuring easy access to personalized risk information with targeted psychological support may mitigate psychological burden as patients reintegrate into society and deal with future COVID‐19 waves. Abstract : In a cohort of inflammatory bowel disease (IBD) patients during the COVID‐19 pandemic, at least moderate depression and anxiety were common, but at similar rates to pre‐pandemic IBD data, and recent general population data. Accessibility of information regarding COVID‐19 risk and reducing that risk appeared protective for depression, anxiety, and stress. There was strong interest in receiving psychological support during and beyond the pandemic.